The correctness and completeness of documentation of parameters on the partographs used by midwives in primary healthcare facilities in midwestern Uganda: A retrospective descriptive study - Archbald Bahizi; Clement Munguiko; Enos Mirembe Masereka (Wiley, 2023)
Abstract Aim This study was conducted to determine the correctness and completeness of documentation of partographs. Design This was a retrospective descriptive study. Methods We included 365 partographs of deliveries conducted from January 1st to October 31st 2019. Data were collected using a checklist and analysed descriptively. The study based on 13 partograph parameters. Results About 8-13 parameters were correctly documented in 71.5 % of the partographs. About 38.9%, 24.7%, 99.7%, 22.5% and 16 % of the partographs had no documentation of obstetric risk factors, foetal heart rate, colour of liquor, uterine contractions and cervical dilatation respectively. About 12.1% of the cervicographs crossed the action line and 61.4% of partographs where cervicographs crossed the action line had no documentation of action(s) taken.